2016
DOI: 10.2967/jnumed.116.178095
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Impact of 68Ga-DOTATATE and 18F-FDG PET/CT on Clinical Management in Patients with Neuroendocrine Tumors

Abstract: This study aimed to assess the clinical impact of 68 Ga-DOTATATE and 18 F-FDG with respect to the management plan and to evaluate the prognostic value of both tracers. Methods: A total of 104 patients (55 male and 49 female; median age, 58 y; range, 20-90 y) with histologically proven neuroendocrine tumors (NETs) underwent both 68 Ga-DOTATATE and 18 F-FDG PET/CT. . Results: The 68 Ga-DOTATATE and 18 F-FDG PET/CT findings were discordant in 65 patients (62.5%) and concordant in 39 patients (37.5%). The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
119
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(136 citation statements)
references
References 36 publications
2
119
1
5
Order By: Relevance
“…However, one concern about the National Oncology PET Registry is that intended management changes may not have been implemented (5,6). In the current study, 68 Ga-DOTATATE PET/CT resulted in intended management changes in 48 of 96 patients (50%), which is comparable to results from prior retrospective studies (2,3,(7)(8)(9)(10)(11). However, no prospective study has elucidated prospectively the rate of implemented management changes.…”
Section: Discussionsupporting
confidence: 74%
“…However, one concern about the National Oncology PET Registry is that intended management changes may not have been implemented (5,6). In the current study, 68 Ga-DOTATATE PET/CT resulted in intended management changes in 48 of 96 patients (50%), which is comparable to results from prior retrospective studies (2,3,(7)(8)(9)(10)(11). However, no prospective study has elucidated prospectively the rate of implemented management changes.…”
Section: Discussionsupporting
confidence: 74%
“…18 F-FDG PET/CT is considered the preferred radiotracer for G3 tumors, as well as for some high-grade G2 tumors. The role of 18 F-FDG PET/CT in G1 tumors or in low-grade G2 tumors is still debated (51). A Ki-67 of at least 10% is often considered the cutoff for proposing the use of 18 F-FDG PET/CT for welldifferentiated G2 NETs (52).…”
Section: F-fdgmentioning
confidence: 99%
“…Vice versa, 68 Ga-SSA PET/CT in cases presenting higher Ki-67 values (.50%), even if positive, will likely not affect management. The added value of 18 F-FDG in welldifferentiated NENs (G1 and G2) is still under debate, and no international consensus has been reached (49)(50)(51)(52)(53).…”
Section: Clinical Valuementioning
confidence: 99%
“…Recently, it was in fact shown that 18 F-FDG PET/CT should be used only in selected cases, with a Ki-67 of less than 12% (53), as in such cases the clinical management uniquely relies on 68 Ga-DOTATATE.…”
Section: Clinical Valuementioning
confidence: 99%